Corporate Disclosure Policy and Analyst Behavior - Lang, Mark H.; Lundholm, Russell J. (The Accounting Review, 1996)
[This paper examines the relations between the disclosure practices of firms, the number of analysts following each firm and properties of the analysts' earnings forecasts. Using data from the Report of the Financial Analysts Federation Corporate Information Committee (FAF Report 1985-89), we provide evidence that firms with more informative disclosure policies have a larger analyst following, more accurate analyst earnings forecasts, less dispersion among individual analyst forecasts and less volatility in forecast revisions. The results enhance our understanding of the role of analysts in capital markets. Further, they suggest that potential benefits to disclosure include increased investor following, reduced estimation risk and reduced information asymmetry, each of which have been shown to reduce a firm's cost of capital in theoretical research.]